Encouraging performance monitoring promotes proactive control in children. Issue 1 (14th June 2019) - Hadley, Lauren V.; Acluche, Frantzy; Chevalier, Nicolas
Abstract: Monitoring progression towards one's goals is essential for efficient cognitive control. Immature performance monitoring may contribute to suboptimal cognitive control engagement in childhood, potentially explaining why children engage control reactively even when proactive control would be more effective. This study investigated whether encouraging children to actively monitor their performance results in more mature control engagement. Electroencephalography data were collected while children and adults performed a flanker task in three conditions in which they were provided no feedback, standard feedback, or were asked to estimate their own feedback. Both age groups accurately estimated their own feedback. Critically, feedback estimation promoted online performance monitoring and proactive engagement of attention and inhibition during the flanker period in children. These findings indicate that proactive control engagement in childhood can be effectively supported by encouraging performance monitoring. Abstract : We tested whether children show inefficient control engagement due to difficulty monitoring their performance. When 5‐7‐year‐olds had to choose appropriate feedback for their performance on a flanker task, they showed increased monitoring and proactive control compared to when they received standard or no feedback. We argue that metacognitive reflection is critical for efficient control engagement.